2016
DOI: 10.5455/aim.2016.24.248-252
|View full text |Cite
|
Sign up to set email alerts
|

Typing of Methicillin Resistant Staphylococcus Aureus Using DNA Fingerprints by Pulsed-field Gel Electrophoresis

Abstract: Background:Methicillin resistant Staphylococcus aureus (MRSA) is responsible for a wide spectrum of nosocomial and community associated infections worldwide. The aim of this study was to analyze MRSA strains from the general population in Canton Sarajevo, B&H.Methods:Our investigation including either phenotypic and genotypic markers such as antimicrobial resistance, pulsed-field gel electrophoresis (PFGE), SCC typing, and Panton-Valentine leukocidin (PVL) detection.Results:Antimicrobial susceptibility: all MR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…DNA microarrays, which have been used for determining virulence or antimicrobial gene presence in diverse bacteria (Hopkins et al, 2007; Carter et al, 2008; Wragg et al, 2009), have also been applied to MRSA, as have WGS (Schouls et al, 2009; Monecke et al, 2011; Piccinini et al, 2012; Shore et al, 2012; Sharma et al, 2016; Sabat et al, 2017). The latter has been particularly useful and is increasingly being used instead of PFGE for purposes such as tracing outbreaks, as well as identifying the most likely source of acquisition, which is an essential component of an effective surveillance system to describe epidemiological trends and infection control strategies (Rebic et al, 2016; Sharma et al, 2016). In addition, although phenotypic methods are easier to perform and interpret, and they are cost effective and widely available, they may be less discriminatory.…”
Section: Whole Genome Sequencing Of Uk Livestock Isolatesmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA microarrays, which have been used for determining virulence or antimicrobial gene presence in diverse bacteria (Hopkins et al, 2007; Carter et al, 2008; Wragg et al, 2009), have also been applied to MRSA, as have WGS (Schouls et al, 2009; Monecke et al, 2011; Piccinini et al, 2012; Shore et al, 2012; Sharma et al, 2016; Sabat et al, 2017). The latter has been particularly useful and is increasingly being used instead of PFGE for purposes such as tracing outbreaks, as well as identifying the most likely source of acquisition, which is an essential component of an effective surveillance system to describe epidemiological trends and infection control strategies (Rebic et al, 2016; Sharma et al, 2016). In addition, although phenotypic methods are easier to perform and interpret, and they are cost effective and widely available, they may be less discriminatory.…”
Section: Whole Genome Sequencing Of Uk Livestock Isolatesmentioning
confidence: 99%
“…In addition, although phenotypic methods are easier to perform and interpret, and they are cost effective and widely available, they may be less discriminatory. Genotypic methods, although more expensive and technically demanding, can provide more detailed characterisation of the isolate (Anjum, 2015; Rebic et al, 2016). Specifically, WGS is a more rapid method for identifying genetic determinants such as virulence and AMR genes, as well as studying phylogenetic relationships between groups of isolates based on the core genome of hundreds of genes, rather than DNA microarray.…”
Section: Whole Genome Sequencing Of Uk Livestock Isolatesmentioning
confidence: 99%
“…With the advent of molecular typing methods, epidemiologists can easily investigate outbreaks of infectious diseases, tracing the transmission of pathogens, and elucidate evolutionary relationships between microorganisms. Several genotyping methods such as amplified fragment length polymorphism [8] , [9] , multiple locus variable-number tandem repeat analysis [8] , [10] , [11] , multilocus sequence typing [12] , [13] , and pulsed-field gel electrophoresis (PFGE) [10] , [14] , [15] , [16] have been successfully applied for epidemiological investigations of MRSA infections worldwide. Of these methods, PFGE is still considered the reference standard fingerprinting method for monitoring and tracking MRSA dissemination in the hospital environment [17] .…”
Section: Introductionmentioning
confidence: 99%
“…Molecular typing tools including staphylococcal protein A (spa) typing, multilocus sequence typing (MLST), pulsed-field gel electrophoresis, staphylococcal cassette chromosome mec (SCC mec ) typing, DNA microarray, and whole genome sequencing (WGS) have been used in the epidemiologic surveillance of MRSA strains to detect and monitor emerging and reemerging infections as well as monitoring geographic spread and shifts of epidemic and endemic clones ( Pfaller, 1999 ; van Belkum et al, 2001 ; Monecke et al, 2011 ; Boswihi et al, 2016 , 2020a , 2020b ; Rebic et al, 2016 ). The application of these typing techniques to type MRSA from different geographic regions have shown that most of the MRSA infections reported worldwide were caused by a limited number of pandemic MRSA clones belonging to clonal complexes 5 (CC5), CC8/ST239, CC22, CC30, and CC45 ( Robinson and Enright, 2003 ; Monecke et al, 2011 ; Guthrie et al, 2020 ) although CA-MRSA isolates belong to more diverse genetic backgrounds compared to HA-MRSA ( Monecke et al, 2011 ; Udo, 2013 ; Tong et al, 2015 ; Guthrie et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%